Their finest ebook A novel. - Evans, Lissa (2024)
From the acclaimed author of  Crooked Heart  comes another "smart, funny, ingenious, revealing tale of London life during the Second World War" ( The Independent ). It is 1940. France has fallen, and only a narrow strip of sea lies between Great Britain and invasion. Now is the time when everyone must do their part. Young copywriter Catrin Cole is drafted into the Ministry of Information to help "write women" into propaganda films—something that the men aren't very good at. Her first assignment is a heart-warming—and completely fabricated—tale of bravery and rescue at Dunkirk. With so many called to service, Catrin and her team must make do with the industry's jaded leftovers: Ambrose Hilliard, third most popular British film-star of 1924; Edith Beadmore, Madame Tussauds wardrobe assistant turned costumier; and Arthur Frith, whose peacetime job as a catering manager has not really prepared him for his unexpected elevation to Special Military Advisor. Now in a serious world, in a nation under siege, they must all swallow their mutual ill-will and unite for the common good, for King and Country, and—in one case—for better or worse. . . . Now a major motion picture starring Gemma Arterton, Sam Claflin, and Bill Nighy Originally published as Their Finest Hour and a Half